Program Men Care Sebagai Upaya Pencegahan Kekerasan Dalam Rumah Tangga : (Studi Deskriptif Pada Yayasan Pulih, Jakarta) - Clara, Clara; Nugroho, Fentiny (UI Scholars Hub, 2016)
Domestic violence is a delicate matter in our society. Many efforts have been made by many institutions to decrease the violence that continues to increase every year. One of them is a prevention effort through a Men Care program that presents the male-engagement. Therefore, this study specifically describes the Men Care program implemented by Yayasan PULIH in Jakarta. This research uses descriptive method with qualitative approach. The results is to describe the forms of male-engagement including advantages and disadvantages faced by Yayasan PULIH in disseminating those issue, as well as strategies undertaken to attract the public participation into the program.